SURVEI LARVA NYAMUK Aedes spp. SEBAGAI VEKTOR PENYAKIT DEMAM BERDARAH DENGUE - Zahara Fadilla; Rustiana Tasya Arining Praja; Febrial Hikmah; NS Widada (Sekolah Tinggi Ilmu Kesehatan Kesetiakawanan Sosial Indonesia, 2022)
Dengue Hemorrhagic Fever (DHF) is still a public health problem in Indonesia. Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus (DENV). Viruses belonging to the Arbovirus group are mostly transmitted in urban areas by Aedes aegypti and Aedes albopictus mosquitoes, Ae. aegypti has a breeding place in water reservoirs, especially clean, not flowing water and not exposed to direct sunlight. This study aims to identify species of mosquito larvae found in water reservoirs in Pamijahan Village, Bogor Regency. The type of research used in this research is descriptive by using a cross sectional design which aims to make observations made for a moment (observed once) with a random sampling system technique. Sampling was carried out in 100 houses located in RT 1, 2, 3, , 5 and 6. The results showed that of the 100 houses examined, 8 of them were positive for mosquito larvae. Mosquito larvae found in water reservoirs are Ae. aegypti and Culex spp. Larvae were found in water storage containers in the form of tubs (62.68%) and jars (22.54%)